2023
DOI: 10.1038/s41388-023-02747-x
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming of cell cycle genes by ACK1 promotes breast cancer resistance to CDK4/6 inhibitor

Abstract: Hormone receptor-positive, HER2-negative advanced breast cancers exhibit high sensitivity to CDK4/6 inhibitors such as palbociclib. However, most patients inevitably develop resistance, thus identification of new actionable therapeutic targets to overcome the recurrent disease is an urgent need. Immunohistochemical studies of tissue microarray revealed increased activation of non-receptor tyrosine kinase, ACK1 (also known as TNK2) in most of the breast cancer subtypes, independent of their hormone receptor sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…ACK1 can promote the growth of BC by interacting with the estrogen receptor (ER) /histone demethylase KDM3A complex [285] . Excessive activation of ACK1 can promote the efficient transcription of cell cycle genes such as CCNB1 and CCNB2, making BC cells resistant to CDK4/6 inhibitors [286] . ACK1 inhibitor ( R )−9bMS can not only inhibit the proliferation of TNBC [287] , but also block the cell cycle and make the growth of drug-resistant HR+/HER2- BC fade [286] .…”
Section: Other Potential Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACK1 can promote the growth of BC by interacting with the estrogen receptor (ER) /histone demethylase KDM3A complex [285] . Excessive activation of ACK1 can promote the efficient transcription of cell cycle genes such as CCNB1 and CCNB2, making BC cells resistant to CDK4/6 inhibitors [286] . ACK1 inhibitor ( R )−9bMS can not only inhibit the proliferation of TNBC [287] , but also block the cell cycle and make the growth of drug-resistant HR+/HER2- BC fade [286] .…”
Section: Other Potential Targetsmentioning
confidence: 99%
“…Excessive activation of ACK1 can promote the efficient transcription of cell cycle genes such as CCNB1 and CCNB2, making BC cells resistant to CDK4/6 inhibitors [286] . ACK1 inhibitor ( R )−9bMS can not only inhibit the proliferation of TNBC [287] , but also block the cell cycle and make the growth of drug-resistant HR+/HER2- BC fade [286] . Previous studies have shown that dasatinib monotherapy is ineffective in the treatment of TNBC, the ORR was 4.7 %, the DCR was 9.3 % and the mPFS was only 8.3 weeks after intervention with either 100 mg or 70 mg of dasatinib twice daily [288] .…”
Section: Other Potential Targetsmentioning
confidence: 99%
“…ACK1 protein encoded by the TNK2 gene is a ubiquitously expressed non-receptor tyrosine kinase that is overexpressed in multiple tumors, including prostate and breast, where its expression is correlated with increased invasiveness and poor prognosis. 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ACK1 is activated by multiple growth factors, including PDGF, FGF, EGF, heregulin, GAS6, and insulin, and its knockdown increases apoptosis. 121 , 125 ACK1 plays a crucial role in increasing WDR5/MLL2 complex-mediated AR transcriptional activation by phosphorylating histone H4 at tyrosine 88 (pY88-H4) in the AR enhancer region.…”
Section: Small-molecule Kinase Inhibitorsmentioning
confidence: 99%